Yahoo Web Search

  1. Sort by

  1. Well in this case the formula would be (n C n-j)*a^(n-j)*(x^2)^j x^8 = (x^2)^4 so j = 4 n = 7 n - j = 3 a = 3 So the...

    2 Answers · Science & Mathematics · 26/07/2009

  2. Assuming that |a(n)| = (j+3) / (j+10), this series diverges by the nth term test, because lim(j→∞) (j+3) / (j+10) = 1, which is nonzero. I hope this helps!

    1 Answers · Science & Mathematics · 06/03/2013

  3. ...a_(1, j) * x_j , Σ(j=1 to n) a_(2, j) * x_j , ..., Σ(j=1 to n) a_(n, j) * x_j) Therefore, f(x) = x₁ Σ(j=1 to n) a_(1, j) * x...

    1 Answers · Science & Mathematics · 12/10/2011

  4. Note that for n, j >0 : |a[n+j] - a[n]| < | a[n+j] - a[n+j-1]| + | a[n+j-1] - a[n+j-2...

    1 Answers · Science & Mathematics · 30/09/2012

  5. ... terms of the binomial expansion of (a + b)^n are C(n,j) * a^(n - j) * b^j Since we want the term for t^8 then n - j = 8. Given n...

    3 Answers · Science & Mathematics · 18/08/2009

  6. The binomial theorm: n Σ n!/j!(n-j)! x^(n-j) a^j = (x+a)^n j=0 --------------------------------------------- The 15th term, will be j=15-1=14...

    3 Answers · Science & Mathematics · 02/05/2013

  7. ... the binomial theorem ...................n (a + b)^12 = Σ C(n, j) a^(n - j) b^(j) ...................j=0 In this case a=1, b = -2x, and n=12. The...

    2 Answers · Science & Mathematics · 17/10/2008

  8. I'm not very sure, but if none of the other answers on here work, seach on google... "letter equation" or "variable equation" and see what comes up.

    3 Answers · Science & Mathematics · 28/09/2009

  9. ...the Binomial Theorem: (a + b)^n = sum(j=0 to n) nCj * a^(n - j) * b^j. If we let a = 1 and b = 3 (a should be 1 to eliminate the n - j exponent...

    2 Answers · Science & Mathematics · 07/08/2010

  10. (a + b )^n has jth term C(n,j) a^(n - j) b^j , C(n, j ) = n! / [ j! ( n-j)! ]...j = 0,1,2,...n ; use it.. note : 3rd term is when j = 2

    1 Answers · Science & Mathematics · 10/03/2015

  1. Try asking your question on Yahoo Answers